Perbedaan Kurikulum 2013 dan Kurikulum Merdeka: Mana yang Lebih Efektif? Differences between the 2013 Curriculum and the Independent Curriculum: Which is More Effective? - Ramadhani, Filiza Alyedia (Maliki Interdisciplinary Journal, 2025)
Curriculum reform is a crucial step in improving the quality of education in Indonesia. This article examines the fundamental differences between the 2013 Curriculum and the Merdeka Curriculum in terms of learning approach, flexibility, character development, assessment methods, and preparedness for 21st-century skills. The 2013 Curriculum focuses on a scientific approach with a standardized structure, while the Merdeka Curriculum emphasizes flexibility, project-based learning, and the development of the Pancasila Student Profile. By comparing these two curricula, this article aims to assess the effectiveness of each within the context of modern learning needs. Analysis suggests that the Merdeka Curriculum holds advantages in adaptability and student character development, although its success heavily relies on teacher readiness and school facilities. This study is expected to provide comprehensive insights for educators and policymakers in selecting or implementing the curriculum best suited to the needs of Indonesian students.